A Review on Load Balancing In Cloud Computing (International Journal of Engineering and Computer Science, 2015)
In today’s world every activity belongs to internet, everything is going online in such a case web applications are playing an important role providing services to the customers and when the application becomes popular, traffic is also growing. Load Balancing is required in such situations to avoid overload. This paper also introduces task scheduling as it is the most important part in cloud computing which aims at meeting users requirements and improving the resource utilization. The purpose of this paper is to review various load balancing, Task scheduling algorithms along with their merits and demerits in detail.